Near-infrared Spectroscopy of the Sun and Solar Analog Star HD 76151: Compiling an Extensive Line List in the Y, J, H, and K Bands - Sena Aleyna Şentürk; Timur Şahin; Ferhat Güney; Selçuk Bilir; Mahmut Marışmak (The Astrophysical Journal)
Determining the physical nature of a star requires precise knowledge of its stellar atmospheric parameters, including effective temperature, surface gravity, and metallicity. This study presents a new atomic line list covering a broad spectral range (1–2.5 μ m; YJHK bands) for iron (Fe) and α -elements (Ca, Mg, Ti, Si) to improve stellar parameter determination using near-infrared (NIR) spectroscopy. We highlight the limitations of existing line lists, stemming primarily from inconsistencies in oscillator strengths for ionized iron lines within the Apache Point Observatory Galactic Evolution Experiment DR17. The line list was validated using the high-resolution and high-quality disk-center NIR spectra of the Sun and its solar analog HD 76151. As a result of the spectroscopic analyses, the effective temperature of HD 76151 was calculated as 5790 ± 170 K, surface gravity as 4.35 ± 0.18 cgs, metal abundance as 0.24 ± 0.09 dex, and microturbulence velocity of ${0.30}_{-0.3}^{+0.5}$ km s ^−1 by combining the optical and NIR line lists. A comparison of the model atmospheric parameters calculated for HD 76151 with the PARSEC isochrones resulted in a stellar mass of ${1.053}_{-0.068}^{+0.056}{M}_{\odot }$ , radius ${1.125}_{-0.011}^{+0.035}{R}_{\odot }$ , and an age of ${5.5}_{-2.1}^{+2.5}$ Gyr. For the first time, kinematic and dynamical orbital analyses of HD 76151 using a combination of Gaia astrometric and spectroscopic data showed that the star was born in a metal-rich region within the solar circle and is a member of the thin disk population. Thus, the slightly metal-rich nature of the star, as reflected in its spectroscopic analysis, was confirmed by dynamical orbital analysis.